Teenagers' Understanding Level about Stunting in Terms of Gender - Asroful Kadafi; Noviyanti Kartika Dewi; Silvia Yula Wardani; Nur Kholifah; Cindi Febi Fatmawati (Indonesian Journal of Global Health Research, 2025)
Stunting is one of the issues that is being focused on by the government. The problem of stunting is a concern and also handled collaboratively with various stakeholder elements. The issue of stunting needs to be introduced to individuals from an early age or before pre-marital age. However, the reality in the field is that there are still many teenagers who do not have sufficient knowledge regarding stunting. This research aims to see the level of students' understanding about stunting. This research uses a quantitative approach, specifically using a survey method. Data sources were obtained from primary sources and analyzed using descriptive statistical analysis and also using different tests. The research results show that students' level of understanding about stunting is at a medium level. And the results of different tests to see whether there are differences in the level of understanding between male and female students show trends that are almost the same or there are no significant differences. It is hoped that the results of this research can be used as a basis for related parties in formulating policies to intervene in stunting prevalence.